Transmissão de sinais OFDM com envelope constante em sistemas ópticos IMDD - Silva, Jair Adriano Lima (2011)
Orthogonal frequency division multiplexing has recently received a special atten-tion in high bit rate long-haul optical transmission systems as an e®ective technique that eliminates all inter-symbol interference caused by chromatic and polarization mode dispersions by electronic dispersion compensation methods. However, like in wireless com- munications context, peak-to-average power ratio (PAPR) reduction techniques are also required because of the distortions caused by nonlinear devices such as Mach-Zehnder optical modulators and the nonlinear ¯ber impairments generated by the inherent large PAPR of OFDM signals, the main drawback of this kind of optical transmissions. A new PAPR reduction technique based on a constant envelope orthogonal frequency division multiplexing (CE-OFDM) approach to mitigate Mach-Zehnder and ¯ber induced nonlinearities in direct-detection optical OFDM (DDO-OFDM) systems is proposed in this thesis. Simulation results obtained by transmission of constant envelope OFDM si- gnals with PAPR = 3 dB through the DDO-CE-OFDM (direct-detection optical - constant envelope - OFDM) system at 10 Gb/s, with 768 subcarriers mapped on 16-QAM (qua- drature amplitude modulation) at 3:54 electrical bandwidth illustrated the capacity of the proposed technique to improves the tradeo® between MZM polarization and optical receiver sensitivity. The experimental results of the DDO-CE-OFDM setup in a back-to- back con¯guration at 1:4 Gb/s using 384 subcarriers mapped on 16-QAM in a bandwidth of 500 MHz proofs its applicability. Simulation results show that the proposed 10 Gb/s DDO-CE-OFDM system, with optical polarization and frequency domain equalizer (FDE), using 16-QAM, 2:66 GHz signal bandwidth and electrical phase modulation index 2¼h = 2 outperforms DDO- OFDM systems as it increases ¯ber nonlinearity tolerance in 960 km of standard single- mode ¯ber link without optical dispersion compensation.